Sampling Phasic Dopamine Signaling with Fast‐Scan Cyclic Voltammetry in Awake, Behaving Rats. Issue 1 (5th January 2015) - Fortin, S.M.; Cone, J.J.; Ng‐Evans, S.; McCutcheon, J.E.; Roitman, M.F.
Abstract: Fast‐scan cyclic voltammetry (FSCV) is an electrochemical technique that permits the in vivo measurement of extracellular fluctuations in multiple chemical species. The technique is frequently utilized to sample sub‐second (phasic) concentration changes of the neurotransmitter dopamine in awake and behaving rats. Phasic dopamine signaling is implicated in reinforcement, goal‐directed behavior, and locomotion, and FSCV has been used to investigate how rapid changes in striatal dopamine concentration contribute to these and other behaviors. This unit describes the instrumentation and construction, implantation, and use of components required to sample and analyze dopamine concentration changes in awake rats with FSCV. © 2015 by John Wiley & Sons, Inc.